Tracking the functional groups responsible for the synthesis of zinc-oxide nanoparticles from zinc nitrate hexahydrate - Krief, Alain; Mohamed, Hamza; Maaza, Malik; Gibaud, Alain (Synthesis)
Heating 1,2-, 1,3- and 1,4-diols with zinc nitrate hexahydrate at 120 °C, delivers explosively, after few minutes, zinc oxide nanoparticles as well as gaseous products such as hydrogen, nitrogen and carbon oxides. They are suspected of being responsible for the formation of nanoparticles. The observed reactivity is dependent upon the alkyl substitution on the diols that leads to suspect but does not prove the formation of organometallic intermediates.